THE USE OF DISCOURSE MARKERS IN SENIOR HIGH SCHOOL EFL STUDENTS"™ ESSAY WRITING ACROSS GENDER - Sari, Ardiana; Basthomi, Yazid; Zen, Evynurul Laily (Jurnal Visi Ilmu Pendidikan, 2025)
Discourse markers (DM) are a growing area of study in gender and language. Scholars have not extensively discussed the relationship between gender and the use of DMs by senior high school students in EFL essays. Therefore, this study aimed to investigate the use of DMs in male and female students"™ essays. This study involved 39 male students"™ essays and 46 female students"™ essays. This study analyzed the differences and similarities in the use of DMs based on Fraser"™s classifications (1999 and 2010) and the inappropriate use of DMs by male and female students. This research revealed that female students used a greater number of DMs and male students used more variations of DMs in their essays. The most frequent DMs used by male and female students are elaborative discourse markers. Semantic incompletion was the most common issue found in applying DMs. Consequently, the teaching practice and teaching material related to DMs require more attention from the teachers.